Nanoimprint glue for optical elements and method for its production
Patent Information
- Application Number
- CN202611495250.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-24
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]为此,本发明提供一种光学元件用的纳米压印胶及其制备方法,以解决现有技术中由于纳米粒子与树脂基体折射率匹配不佳而导致的难以兼顾高折射率和高透光率的问题
本发明通过对-[(4-乙烯基苯基)甲基]膦酸修饰二氧化钛-环三磷腈骨架-二硫醇的三元协同增加丙烯酸酯树脂体系折射率,结合紫外线-热双固化,在提升了二氧化钛纳米颗粒在丙烯酸酯体系中的相容性、保留压印胶的高透光率、低雾度的同时提升了其折射率。此外,环三磷腈骨架结合环氧基-二硫醇-丙烯酸酯双层交联网络显著降低了胶层的固化收缩率,使制备的纳米压印胶可广泛应用于光学元件的纳米压印制造。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of micro-nano fabrication materials technology, specifically to a nanoimprint adhesive for optical components and its preparation method. Background Technology
[0002] Nanoimprint lithography is a low-cost, high-throughput imprinting technique with sub-micron resolution, and it is crucial for fabricating microarray lenses, automotive head-up display (HUD) gratings, and semiconductor micro / nanostructures. The imprinting adhesive is the core medium for image transfer, and its parameters such as refractive index, viscosity, and transmittance directly determine the optical performance and precision of the device. UV-curable nanoimprinting adhesives are currently the most commonly used imprinting adhesives, offering advantages such as room temperature operation, fast curing speed, high resolution, high image fidelity, and excellent optical performance.
[0003] Currently, commercially available high-refractive-index imprinting adhesives are usually doped with a large number of inorganic nanoparticles. Improper control of nanoparticle size, lack of effective surface modification, or poor matching of refractive index with the resin matrix usually result in high system viscosity, poor leveling, high haze, and low light transmittance. On the other hand, low-refractive-index imprinting adhesives are difficult to balance solid content and film uniformity, and have insufficient dispersion control, which affects image clarity.
[0004] Therefore, there is an urgent need for a high-performance imprinting adhesive with high refractive index, high light transmittance, and low haze to solve the above problems. Summary of the Invention
[0005] Therefore, the present invention provides a nanoimprint adhesive for optical components and its preparation method, in order to solve the problem in the prior art that it is difficult to achieve both high refractive index and high light transmittance due to poor refractive index matching between nanoparticles and resin matrix.
[0006] To achieve the above objectives, the present invention provides the following technical solution: According to a first aspect of the present invention, a nanoimprint adhesive for optical elements is provided, specifically comprising the following components in parts by weight: 10-20 parts of modified titanium dioxide nanoparticles, 10-20 parts of epoxy-modified cyclotriphosphazene, 30-40 parts of acrylate prepolymer, 3-7 parts of curing agent, 0.1-1 parts of photoinitiator, 1-3 parts of organic base, and 20-30 parts of reactive diluent.
[0007] Furthermore, the modified titanium dioxide nanoparticles are titanium dioxide nanoparticles modified with p-[(4-vinylphenyl)methyl]phosphonic acid, the epoxy-modified cyclotriphosphazene is hexaglycidylcyclotriphosphazene, the curing agent is dithiol, the organic base is triethylamine, the photoinitiator is 2-isopropylthioxanthone, and the reactive diluent is trimethylolpropane triacrylate.
[0008] Furthermore, the dithiol is 1,3-benzenedithiophenol; the particle size of the titanium dioxide nanoparticles in the modified titanium dioxide nanoparticles is 1-10 nm.
[0009] Furthermore, the acrylate prepolymer has a viscosity of 2000-5000 mPa·s, a haze of ≤2.0, and a refractive index of ≥1.4.
[0010] Furthermore, the nanoimprint adhesive undergoes UV curing followed by thermal curing during the curing process; the UV curing conditions are a wavelength of 365nm and a heat treatment rate of 50-200mW / cm². 2 Irradiate for 10-60 seconds; the heat curing conditions are heating at 60-80℃ for 1-4 hours.
[0011] According to a second aspect of the present invention, a method for preparing a nanoimprint adhesive for optical elements is provided, which specifically includes the following steps: S1. Preparation of modified titanium dioxide nanoparticles: Modified titanium dioxide nanoparticles were obtained by modifying titanium dioxide nanoparticles with p-[(4-vinylphenyl)methyl]phosphonic acid. S2, Preparation of epoxy-modified cyclotriphosphazene: The epoxy-modified cyclotriphosphazene was obtained by reacting glycidol with hexachlorocyclotriphosphazene. S3. Preparation of nanoimprint adhesive: Modified titanium dioxide nanoparticles, epoxy-modified cyclotriphosphazene, acrylate prepolymer, curing agent, organic base, reactive diluent and photoinitiator are mixed to obtain nanoimprint adhesive.
[0012] Furthermore, step S1 specifically includes the following steps: Titanium dioxide was dispersed in deionized water at pH 2-3 to a final concentration of 10-20 g / L, and p-[(4-vinylphenyl)methyl]phosphonic acid was added to a final concentration of 6-8 mM. The mixture was reacted at 70-90℃ for 48-60 h. After the reaction, the mixture was centrifuged at 3000-7000 rpm for 5-15 min. The precipitate was washed 2-3 times with deionized water and dried at 60-80℃ for 6-12 h to obtain modified titanium dioxide nanoparticles.
[0013] Furthermore, step S2 specifically includes the following steps: Tetrahydrofuran was divided into three equal volumes. Glycidol and hexachlorocyclotriphosphazene were each dissolved in one volume of tetrahydrofuran to obtain solutions of glycidol and hexachlorocyclotriphosphazene; the molar ratio of glycidol to hexachlorocyclotriphosphazene was 8:1; the mass-to-volume ratio of hexachlorocyclotriphosphazene and glycidol to tetrahydrofuran was 1 g:4 mL. Sodium hydride was dispersed in the remaining tetrahydrofuran, and the amount of sodium hydride added was 1.1 times that of glycidol to obtain a solution of... Sodium hydride dispersion; slowly add propylene oxide solution dropwise to sodium hydride dispersion, stir at room temperature for 30 min, then add hexachlorocyclotriphosphazene solution dropwise, the dropwise addition rate of propylene oxide and hexachlorocyclotriphosphazene solution is ≤0.1 L / h; after the dropwise addition is completed, react at 25-35℃ under nitrogen atmosphere for 3-6 h, after the reaction is completed, remove tetrahydrofuran by vacuum distillation, wash the crude product 2-3 times with dichloromethane, and then remove dichloromethane by vacuum distillation to obtain epoxy modified cyclotriphosphazene.
[0014] Furthermore, step S3 specifically includes the following steps: Modified titanium dioxide nanoparticles, epoxy-modified cyclotriphosphazene, acrylate prepolymer, and reactive diluent were stirred in a planetary mixer at 60-80℃ for 30-60 min, then cooled to 20-40℃ and intermittently treated with a probe-type ultrasonic processor at 200W for 10 min; the intermittent treatment consisted of 5 s treatments followed by a 5 s interval before continuing treatment; a curing agent, organic base, and photoinitiator were added, and stirring was continued for 10-20 min to obtain the nanoimprint adhesive.
[0015] According to a third aspect of the present invention, an application of a nanoimprint adhesive for optical elements in the fabrication of optical elements is provided.
[0016] The present invention has the following advantages: This invention increases the refractive index of acrylate resin systems through a ternary synergistic effect of modifying a titanium dioxide-cyclotriphosphazene skeleton-dithiol system with -[(4-vinylphenyl)methyl]phosphonic acid. Combined with UV-thermal dual curing, this improves the compatibility of titanium dioxide nanoparticles in acrylate systems, retains the high transmittance and low haze of the imprinting adhesive, and simultaneously enhances its refractive index. Furthermore, the combination of the cyclotriphosphazene skeleton with an epoxy-dithiol-acrylate bilayer crosslinking network significantly reduces the curing shrinkage of the adhesive layer, enabling the prepared nanoimprinting adhesive to be widely used in the nanoimprinting fabrication of optical components. Detailed Implementation
[0017] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0018] According to a first aspect of the present invention, a nanoimprint adhesive for optical elements is provided, specifically comprising the following components in parts by weight: 10-20 parts of modified titanium dioxide nanoparticles, 10-20 parts of epoxy-modified cyclotriphosphazene, 30-40 parts of acrylate prepolymer, 3-7 parts of curing agent, 0.1-1 parts of photoinitiator, 1-3 parts of organic base, and 20-30 parts of reactive diluent.
[0019] Among them, the modified titanium dioxide nanoparticles are titanium dioxide nanoparticles modified with p-[(4-vinylphenyl)methyl]phosphonic acid, the epoxy-modified cyclotriphosphazene is hexaglycidylcyclotriphosphazene, the curing agent is dithiol, the organic base is triethylamine, the photoinitiator is 2-isopropylthioxanthrone, and the reactive diluent is trimethylolpropane triacrylate.
[0020] The dithiol is 1,3-benzenedithiophenol; the particle size of the titanium dioxide nanoparticles in the modified titanium dioxide nanoparticles is 1-10 nm.
[0021] The acrylate prepolymer has a viscosity of 2000-5000 mPa·s, a haze of ≤2.0, and a refractive index of ≥1.4.
[0022] The nano-imprint adhesive undergoes UV curing followed by thermal curing during the curing process; the UV curing conditions are a wavelength of 365nm and a heat treatment rate of 50-200mW / cm². 2 Irradiate for 10-60 seconds; heat curing conditions are heating at 60-80℃ for 1-4 hours.
[0023] According to a second aspect of the present invention, a method for preparing a nanoimprint adhesive for optical elements is provided, which specifically includes the following steps: S1. Preparation of modified titanium dioxide nanoparticles: Modified titanium dioxide nanoparticles were obtained by modifying titanium dioxide nanoparticles with p-[(4-vinylphenyl)methyl]phosphonic acid. S2, Preparation of epoxy-modified cyclotriphosphazene: The epoxy-modified cyclotriphosphazene was obtained by reacting glycidol with hexachlorocyclotriphosphazene. S3. Preparation of nanoimprint adhesive: Modified titanium dioxide nanoparticles, epoxy-modified cyclotriphosphazene, acrylate prepolymer, curing agent, organic base, reactive diluent and photoinitiator are mixed to obtain nanoimprint adhesive.
[0024] Step S1 specifically includes the following steps: Titanium dioxide was dispersed in deionized water at pH 2-3 to a final concentration of 10-20 g / L, and p-[(4-vinylphenyl)methyl]phosphonic acid was added to a final concentration of 6-8 mM. The mixture was reacted at 70-90℃ for 48-60 h. After the reaction, the mixture was centrifuged at 3000-7000 rpm for 5-15 min. The precipitate was washed 2-3 times with deionized water and dried at 60-80℃ for 6-12 h to obtain modified titanium dioxide nanoparticles.
[0025] Step S2 specifically includes the following steps: Tetrahydrofuran was divided into three equal volumes. Glycidol and hexachlorocyclotriphosphazene were each dissolved in one volume of tetrahydrofuran to obtain solutions of glycidol and hexachlorocyclotriphosphazene; the molar ratio of glycidol to hexachlorocyclotriphosphazene was 8:1; the mass-to-volume ratio of hexachlorocyclotriphosphazene and glycidol to tetrahydrofuran was 1 g:4 mL. Sodium hydride was dispersed in the remaining tetrahydrofuran, and the amount of sodium hydride added was 1.1 times that of glycidol to obtain a solution of... Sodium hydride dispersion; slowly add propylene oxide solution dropwise to sodium hydride dispersion, stir at room temperature for 30 min, then add hexachlorocyclotriphosphazene solution dropwise, the dropwise addition rate of propylene oxide and hexachlorocyclotriphosphazene solution is ≤0.1 L / h; after the dropwise addition is completed, react at 25-35℃ under nitrogen atmosphere for 3-6 h, after the reaction is completed, remove tetrahydrofuran by vacuum distillation, wash the crude product 2-3 times with dichloromethane, and then remove dichloromethane by vacuum distillation to obtain epoxy modified cyclotriphosphazene.
[0026] Step S3 specifically includes the following steps: Modified titanium dioxide nanoparticles, epoxy-modified cyclotriphosphazene, acrylate prepolymer, and reactive diluent were stirred in a planetary mixer at 60-80℃ for 30-60 min, then cooled to 20-40℃ and intermittently treated with a probe-type ultrasonic processor at 200W for 10 min; the intermittent treatment consisted of 5 s treatments followed by a 5 s interval before continuing treatment; a curing agent, organic base, and photoinitiator were added, and stirring was continued for 10-20 min to obtain the nanoimprint adhesive.
[0027] According to a third aspect of the present invention, an application of a nanoimprint adhesive for optical elements in the fabrication of optical elements is provided.
[0028] To better illustrate the technical path of the present invention, the following embodiments and comparative examples are provided.
[0029] Example 1 S1. Preparation of modified titanium dioxide nanoparticles: 45g of titanium dioxide (purchased from Shanghai Yuanjiang Chemical Co., Ltd., CAS: 13463-67-7, particle size: 5-10nm, anatase type, model: A32000) was dispersed in 3L of deionized water at pH 2.5. p-[(4-vinylphenyl)methyl]phosphonic acid (purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd., CAS: 53459-43-1) was added to a final concentration of 7mM. The mixture was reacted at 80℃ for 60h. After the reaction, the mixture was centrifuged at 5000rpm for 10min. The precipitate was washed three times with deionized water and dried at 70℃ for 9h to obtain modified titanium dioxide nanoparticles. S2, Preparation of epoxy-modified cyclotriphosphazene: 270.4 mL of tetrahydrofuran was divided into three equal volumes. 42.61 g of glycidol and 25 g of hexachlorocyclotriphosphazene were dissolved in one volume of tetrahydrofuran to obtain solutions of glycidol and hexachlorocyclotriphosphazene (purchased from Wuhan Shuer Biotechnology Co., Ltd., CAS: 940-71-6, HCCTP). 15.19 g of sodium hydride was dispersed in the remaining tetrahydrofuran to obtain a sodium hydride dispersion. The glycidol solution was slowly added dropwise to the sodium hydride dispersion, and the mixture was stirred at room temperature for 30 min. Then, the hexachlorocyclotriphosphazene solution was added dropwise at a rate ≤0.1 L / h. After the addition was complete, the mixture was reacted at 30 °C under a nitrogen atmosphere for 4 h. After the reaction, tetrahydrofuran was removed by vacuum distillation. The crude product was washed three times with dichloromethane, and then dichloromethane was removed by vacuum distillation to obtain epoxy-modified cyclotriphosphazene. S3. Preparation of nanoimprint adhesive: 30g of modified titanium dioxide nanoparticles, 30g of epoxy-modified cyclotriphosphazene, 75g of acrylate prepolymer (purchased from Sartoma (Guangzhou) Chemical Co., Ltd., model: CN2254NS, viscosity at 65℃: 2500-4500mPa·s, refractive index at 25℃: 1.53, haze 1.7%), and 50g of trimethylolpropane triacrylate (purchased from Hubei Langbowan Biopharmaceutical Co., Ltd., CAS: 15625-89-5) were stirred in a planetary mixer at 70℃ for 45 minutes. After 10 min, the temperature was lowered to 30℃ and intermittently processed for 10 min using a probe-type ultrasonic processor at 200W. The intermittent processing consisted of 5 s processing followed by a 5 s interval before continuing processing. 10 g of 1,3-benzenedithiophenol (purchased from Tokyo Chemical Industry Co., Ltd., CAS: 626-04-0), 4 g of triethylamine, and 1 g of 2-isopropylthioxanthone (purchased from Wuhan Shuer Biotechnology Co., Ltd., CAS: 5495-84-1) were added and stirred for 15 min to obtain the nanoimprint adhesive.
[0030] Example 2 This embodiment is based on Example 1, except that it includes the following components by mass: 30g of modified titanium dioxide nanoparticles, 30g of epoxy-modified cyclotriphosphazene, 68g of acrylate prepolymer, 50g of trimethylolpropane triacrylate, 14g of 1,3-benzenedithiophenol, 2g of 2-isopropylthioxanthrone, and 6g of triethylamine. The other specific parameters are the same as in Example 1.
[0031] Example 3 This embodiment is based on Example 1, except that it includes the following mass components: 30g of modified titanium dioxide nanoparticles, 30g of epoxy-modified cyclotriphosphazene, 80g of acrylate prepolymer, 6g of 1,3-benzenedithiophenol, 51.8g of trimethylolpropane triacrylate, 0.2g of 2-isopropylthioxanthrone, and 2g of triethylamine. The other specific parameters are the same as in Example 1.
[0032] Example 4 This embodiment is based on Example 1, except that it includes the following mass components: 22.5g of modified titanium dioxide nanoparticles, 22.5g of epoxy-modified cyclotriphosphazene, 80g of acrylate prepolymer, 10g of 1,3-benzenedithiophenol, 60g of trimethylolpropane triacrylate, 1g of 2-isopropylthioxanthrone, and 4g of triethylamine. The other specific parameters are the same as in Example 1.
[0033] Example 5 This embodiment is based on Example 1, except that it includes the following components by mass: 40g of modified titanium dioxide nanoparticles, 40g of epoxy-modified cyclotriphosphazene, 60g of acrylate prepolymer, 10g of 1,3-benzenedithiophenol, 45g of trimethylolpropane triacrylate, 1g of 2-isopropylthioxanthrone, and 4g of triethylamine. The other specific parameters are the same as in Example 1.
[0034] Comparative Example 1 This comparative example is based on Example 1, except that it includes the following components by mass: 30g of epoxy-modified cyclotriphosphazene, 105g of acrylate prepolymer, 10g of 1,3-benzenedithiophenol, 50g of trimethylolpropane triacrylate, 1g of 2-isopropylthioxanthrone, and 4g of triethylamine. The other specific parameters are the same as in Example 1.
[0035] Comparative Example 2 This comparative example is based on Example 1, except that it includes the following components by weight: 30g of modified titanium dioxide nanoparticles, 105g of acrylate prepolymer, 50g of trimethylolpropane triacrylate, 10g of 1,3-benzenedithiophenol, 1g of 2-isopropylthioxanthrone, and 4g of triethylamine.
[0036] Comparative Example 3 This comparative example is based on Example 1, except that it includes the following components by weight: 127g of acrylate prepolymer, 50g of trimethylolpropane triacrylate, 15g of 1,3-benzenedithiophenol, 2g of 2-isopropylthioxanthrone, and 6g of triethylamine.
[0037] Comparative Example 4 This comparative example is based on Example 1, except that it includes the following mass components: 30g of titanium dioxide nanoparticles, 30g of epoxy-modified cyclotriphosphazene, 75g of acrylate prepolymer, 50g of trimethylolpropane triacrylate, 10g of 1,3-benzenedithiophenol, 1g of 2-isopropylthioxanthrone, and 4g of triethylamine. The other specific parameters are the same as in Example 1.
[0038] Comparative Example 5 This comparative example is based on Example 1, except that it includes the following mass components: 30g of titanium dioxide nanoparticles, 110g of acrylate prepolymer, 50g of trimethylolpropane triacrylate, 1g of 2-isopropylthioxanthone, 4g of triethylamine, and 5g of KH-570. The other specific parameters are the same as in Example 1.
[0039] Test Example 1 To evaluate the viscosity and curing shrinkage of the prepared nanoimprint adhesive before curing, the viscosity at room temperature before curing was determined according to GB / T 22235-2008 "Determination of viscosity of liquids", and the curing shrinkage was determined according to GB / T 1033.1-2008 "Determination of density of non-foamed plastics - Part 1: Impregnation method, liquid specific gravity bottle method and titration method". The results are recorded in Table 1. The curing conditions are as follows: UV curing followed by heat curing; the UV curing conditions are 365nm wavelength and 200mW / cm². 2 Irradiate for 45 seconds; heat curing conditions are heating at 70°C for 3 hours.
[0040] Table 1. Viscosity and curing shrinkage of nanoimprint adhesive before curing
[0041] As shown in Table 1, the viscosity of the nanoimprint adhesives prepared in Examples 1-5 of this invention is all within the range of 500-1500 mPa·s, and the curing shrinkage rate is <3%, exhibiting good process flowability and dimensional stability. Compared with the example group, the comparative example group shows a higher curing shrinkage rate of 3.3%-5.7%, while the viscosity varies depending on the missing component.
[0042] The viscosity of the nanoimprint embossing adhesive showed a significant correlation with the content and surface properties of the modified titanium dioxide nanoparticles. Data from Examples 1, 5, and Comparative Example 3 showed that Example 5, with the highest amount of modified titanium dioxide nanoparticles, exhibited the second highest viscosity among all samples, at 1199 mPa·s, while Comparative Example 3, without modified titanium dioxide nanoparticles, showed the lowest viscosity, at only 476 mPa·s. However, Comparative Example 4, where unmodified titanium dioxide nanoparticles were used instead of the modified nanoparticles, saw its viscosity increase to 904 mPa·s, indicating a positive correlation between the viscosity of the imprint embossing adhesive and the amount of modified titanium dioxide nanoparticles added. Furthermore, the phosphonic acid and the modification of titanium dioxide significantly improved its compatibility in the acrylate system, reducing the system viscosity. In addition, the amount of modified titanium dioxide nanoparticles added showed opposite trends in its effect on the viscosity and curing shrinkage rate of the imprint embossing adhesive. This is because the change in viscosity of the adhesive is mainly determined by the physical interaction between particles. Titanium dioxide, as a rigid inorganic filler, does not participate in polymerization shrinkage. After modification, the phosphonic acid modified on its surface is anchored in the resin network through chemical bonding, which restricts the movement of polymer molecular chain segments, thereby inhibiting curing volume shrinkage and increasing viscosity.
[0043] Compared to Example 1, Comparative Example 2 showed a viscosity increase of 300 mPa·s and a curing shrinkage rate increase of 2.2%, indicating that the epoxy-modified cyclotriphosphazene skeleton and the epoxy-thiol combined thiol-olefin dual-curing system can effectively reduce the curing shrinkage rate and viscosity of the system. The results of Comparative Example 4 (dual-curing system, unmodified titanium dioxide nanoparticles) and Comparative Example 5 (single thiol-olefin curing, unmodified titanium dioxide nanoparticles) also confirm this.
[0044] Test Example 2 The refractive index of the cured adhesive layer at 589 nm was determined according to the method of GB / T 39691-2020 "Determination of refractive index of plastics". The transmittance and haze of the adhesive layer were determined according to the method of GB / T 2410-2008. The curing conditions were the same as those in Test Example 1. The results are recorded in Table 2.
[0045] Table 2 Refractive index, haze, and transmittance of the printing adhesive
[0046] It can be seen that the imprinting adhesives prepared in the example groups all exhibited good refractive indices, ranging from 1.648 to 1.751, while the refractive indices of the comparative examples, which lacked or had their components replaced, decreased to 1.528-1.615. This is due to the synergistic effect of the modified titanium dioxide nanoparticles and the dual curing system of cyclotriphosphazene skeleton-dithiol-acrylate in the example groups. Compared with Example 1, the absolute values of the refractive indices of Comparative Examples 1-4 decreased by 0.154, 0.092, 0.179, and 0.118, respectively, confirming this point. That is, the absence of any key component leads to a significant decrease in refractive index, and the degree of decrease in refractive index varies depending on the missing component. Compared with Comparative Example 3, the increase in refractive index of Example 1 is significantly higher than the sum of the increases in Comparative Examples 1 and 2 compared to Comparative Example 3, indicating that there is a synergistic effect between the modified titanium dioxide nanoparticles and the epoxy-modified cyclotriphosphazene on the refractive index improvement of the imprinting adhesive.
[0047] In addition, except for Comparative Examples 4 and 5, the imprinting adhesives prepared in each group all exhibited good transmittance and haze, with transmittance >96% and haze <0.2%. This indicates that incorporating cyclotriphosphazene or thiol curing agents into the acrylate system does not affect the transmittance of the adhesive layer. However, the titanium dioxide nanoparticles without phosphonic acid surface modification have poor compatibility with the organic system, resulting in a significant decrease in transmittance and a significant increase in haze of the adhesive layer.
[0048] In summary, the synergistic effect of modified titanium dioxide nanoparticles and epoxy-modified cyclotriphosphazene significantly improves the refractive index while effectively suppressing the thickening effect of the system caused by inorganic nanoparticles, thus ensuring good process leveling properties of the printing adhesive.
[0049] Although the present invention has been described in detail above with general descriptions and specific embodiments, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention.
Claims
1. A nanoimprint adhesive for optical components, characterized in that, Specifically, it includes the following components by weight: 10-20 parts modified titanium dioxide nanoparticles, 10-20 parts epoxy-modified triphosphazene, 30-40 parts acrylate prepolymer, 3-7 parts curing agent, 0.1-1 parts photoinitiator, 1-3 parts organic base, and 20-30 parts reactive diluent.
2. The nanoimprint adhesive as described in claim 1, characterized in that, The modified titanium dioxide nanoparticles are titanium dioxide nanoparticles modified with p-[(4-vinylphenyl)methyl]phosphonic acid, the epoxy-modified cyclotriphosphazene is hexaglycidylcyclotriphosphazene, the curing agent is dithiol, the organic base is triethylamine, the photoinitiator is 2-isopropylthioxanthrone, and the reactive diluent is trimethylolpropane triacrylate.
3. The nanoimprint adhesive as described in claim 2, characterized in that, The dithiol is 1,3-benzenedithiophenol; the particle size of the titanium dioxide nanoparticles in the modified titanium dioxide nanoparticles is 1-10 nm.
4. The nanoimprint adhesive as described in claim 1, characterized in that, The acrylate prepolymer has a viscosity of 2000-5000 mPa·s, a haze of ≤2.0, and a refractive index of ≥1.
4.
5. The nanoimprint adhesive as described in claim 1, characterized in that, The nanoimprint adhesive undergoes UV curing followed by thermal curing during the curing process; the UV curing conditions are 365nm wavelength and 50-200mW / cm². 2 Irradiate for 10-60 seconds; the heat curing conditions are heating at 60-80℃ for 1-4 hours.
6. A method for preparing a nanoimprint adhesive for optical components, used to prepare the nanoimprint adhesive according to any one of claims 1-5, characterized in that, Specifically, the following steps are included: S1. Preparation of modified titanium dioxide nanoparticles: Modified titanium dioxide nanoparticles were obtained by modifying titanium dioxide nanoparticles with p-[(4-vinylphenyl)methyl]phosphonic acid. S2, Preparation of epoxy-modified cyclotriphosphazene: The epoxy-modified cyclotriphosphazene was obtained by reacting glycidol with hexachlorocyclotriphosphazene. S3. Preparation of nanoimprint adhesive: Modified titanium dioxide nanoparticles, epoxy-modified cyclotriphosphazene, acrylate prepolymer, curing agent, organic base, reactive diluent and photoinitiator are mixed to obtain nanoimprint adhesive.
7. The method for preparing the nanoimprint adhesive as described in claim 6, characterized in that, Step S1 in detail Includes the following steps: Titanium dioxide was dispersed in deionized water at pH 2-3 to a final concentration of 10-20 g / L, and p-[(4-vinylphenyl)methyl]phosphonic acid was added to a final concentration of 6-8 mM. The mixture was reacted at 70-90℃ for 48-60 h. After the reaction, the mixture was centrifuged at 3000-7000 rpm for 5-15 min. The precipitate was washed 2-3 times with deionized water and dried at 60-80℃ for 6-12 h to obtain modified titanium dioxide nanoparticles.
8. The method for preparing the nanoimprint adhesive as described in claim 6, characterized in that, Step S2 specifically includes the following steps: Tetrahydrofuran was divided into three equal volumes. Glycidol and hexachlorocyclotriphosphazene were each dissolved in one volume of tetrahydrofuran to obtain solutions of glycidol and hexachlorocyclotriphosphazene; the molar ratio of glycidol to hexachlorocyclotriphosphazene was 8:1; the mass-to-volume ratio of hexachlorocyclotriphosphazene and glycidol to tetrahydrofuran was 1 g:4 mL. Sodium hydride was dispersed in the remaining tetrahydrofuran, and the amount of sodium hydride added was 1.1 times that of glycidol to obtain a solution of... Sodium hydride dispersion; slowly add propylene oxide solution dropwise to sodium hydride dispersion, stir at room temperature for 30 min, then add hexachlorocyclotriphosphazene solution dropwise, the dropwise addition rate of propylene oxide and hexachlorocyclotriphosphazene solution is ≤0.1 L / h; after the dropwise addition is completed, react at 25-35℃ under nitrogen atmosphere for 3-6 h, after the reaction is completed, remove tetrahydrofuran by vacuum distillation, wash the crude product 2-3 times with dichloromethane, and then remove dichloromethane by vacuum distillation to obtain epoxy modified cyclotriphosphazene.
9. The method for preparing the nanoimprint adhesive as described in claim 6, characterized in that, Step S3 specifically includes the following steps: Modified titanium dioxide nanoparticles, epoxy-modified cyclotriphosphazene, acrylate prepolymer, and reactive diluent were stirred in a planetary mixer at 60-80℃ for 30-60 min, then cooled to 20-40℃ and intermittently treated with a probe-type ultrasonic processor at 200W for 10 min; the intermittent treatment consisted of 5 s treatments followed by a 5 s interval before continuing treatment; a curing agent, organic base, and photoinitiator were added, and stirring was continued for 10-20 min to obtain the nanoimprint adhesive.
10. The use of the nanoimprint adhesive for optical elements according to any one of claims 1-5 in the fabrication of optical elements.